2008
DOI: 10.1186/1471-244x-8-28
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and Disruptive behavior scores – associations with MAO-A and 5-HTT genes and with platelet MAO-B activity in adolescents

Abstract: BackgroundPharmacological and genetic studies suggest the importance of the dopaminergic, serotonergic, and noradrenergic systems in the pathogenesis of Attention Deficit Hyperactivity Disorder (ADHD) and Disruptive Behavior Disorder (DBD). We have, in a population-based sample, studied associations between dimensions of the ADHD/DBD phenotype and Monoamine Oxidase B (MAO-B) activity in platelets and polymorphisms in two serotonergic genes: the Monoamine Oxidase A Variable Number of Tandem Repeats (MAO-A VNTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
(45 reference statements)
4
22
1
2
Order By: Relevance
“…By contrast with the earlier literature, where ND and CD were linked to same genetic background [23,30], ND was not found here to be related to either the subscale of "aggression towards people and animals" or the "solitary CD" or "childhood-onset CD" subtypes, in spite of the fact that these subtypes are known to be related to life-long persistent antisocial behaviour [31], which has a strong biological background [32]. It is interesting, however, that although the correlation between the number of CD symptoms and the level of ND was present in both genders, our results suggest that aggressive CD and ND are not related, at least in adolescence (before 18 years).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…By contrast with the earlier literature, where ND and CD were linked to same genetic background [23,30], ND was not found here to be related to either the subscale of "aggression towards people and animals" or the "solitary CD" or "childhood-onset CD" subtypes, in spite of the fact that these subtypes are known to be related to life-long persistent antisocial behaviour [31], which has a strong biological background [32]. It is interesting, however, that although the correlation between the number of CD symptoms and the level of ND was present in both genders, our results suggest that aggressive CD and ND are not related, at least in adolescence (before 18 years).…”
Section: Discussioncontrasting
confidence: 84%
“…Both the initiation of smoking and continuous smoking have been shown to have a strong genetic heritability of around 50%, as also has CD [20,21,22], and a group of candidate genes have been studied in an attempt to explain both phenomena [20,23,24]. Dopaminergic and serotonergic systems have been considered on account of their influence on smoking/nicotine dependence and CD, in view of the fact that, among many other things, both of these neurotransmitter systems mediate a wide spectrum of cognitive functions such as problem-solving under stress [25,26], leading to the hypothesis that dysfunction in these systems can cause aggressive behaviour [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, a population-based twin study found that homozygosity for the short MAOA-mVNTR allele was associated with disruptive behavior in boys 60 .…”
Section: Conduct Disorder and Aggressive/impulsive Behaviormentioning
confidence: 98%
“…In girls with ADHD, low platelet MAO-B activity was associated with symptoms of oppositional defiant disorder, and short mao-a VNTR variants were associated with disruptive behavior in boys (Malmberg et al 2008). Correlation of enzyme expression in the brain with that in peripheral tissues, however, has not been completely confirmed (Winblad et al 1979), suggesting the limits to interpreting platelet MAO-B activity as a marker of 5-HT and NE turnover in the brain.…”
Section: Discussionmentioning
confidence: 94%